Antioxidant activity and chemical composition of extract from Myxopyrum smilacifolium trunk - Hiếu, Lê Trung; Nguyễn Minh, Nhung; Lê Lâm, Sơn; Nguyễn Quang, Mẫn; Hồ Xuân Anh, Vũ; Trần Thanh, Minh; Nguyễn Việt, Thắng; Nguyễn Thị, Như; Trần Thị Văn, Thi (Hue University Journal of Science: Natural Science, 2023)
Myxopyrum smilacifolium is an infused herb commonly used in folk remedies in Vietnam and other countries worldwide to treat nervous disorders, rheumatism, and bronchitis. The antioxidant potential of the ethanol extract was evaluated through DPPH and ABTS radical scavenging and the total antioxidant capacity method. The results show that the extract possesses high antioxidant activity, with a low IC50 value (IC50 = 42.23 and 46.57 μg·mL–1 for DPPH and ABTS radical scavenging capacity), and the total antioxidant capacity was 207.28 ± 8.43 mg GA·g–1. The chemical composition of Myxopyrum smilacifolium trunk extract, namely the total phenolics, total flavonoid, polysaccharides, and triterpenoid, was examined by using the colourimetric method. Their quantities are equivalent to 149.12 ± 1.36 mg GA·g–1 and 91.39 ± 1.33 mg QE·g–1, 5.12 ± 0.07%, and 35.22 ± 0.81 mg oleanolic acid·g–1, respectively. Specifically, the total triterpenoid content of Myxopyrum smilacifolium trunk was reported for the first time.